PENGARUH KECERDASAN SPIRITUAL TERHADAP KOMITMEN ORGANISASIONAL MELALUI KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA KARYAWAN PERBANKAN SYARIAH DI KOTA BANDA ACEH - Fiqi Rizkia Akbar, Nurlina (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2017)
The aim of this study is to investigate the effect of spiritual intelligence on organizational commitment through job satisfaction as mediator variable. The present study was conducted on 78 employees of sharia banking in Banda Aceh City.  The sampling using saturation method. This study uses two variables, namely the independent variable and the dependent variable. The independent variable in this study are: spiritual intelligence and job satisfaction while the dependent variable is organizational commitment. Questionnaires measured using a Likert’s Scale. Test validity, reliability, normality, multikolinearity and analysis regression using SPSS Statistics 17.0. The findings indicate that spiritual intelligence has a negative influence on organizational commitment; spiritual intelligence has a positive influence on job satisfaction; job satisfaction has a positive influence on organizational commitment. Spiritual intelligence and job satisfaction has a positive influence on organizational commitment. As a result, the effect of spiritual intelligence on organizational commitment is mediated by job satisfaction. Keywords: spiritual intelligence, organizational commitment, job satisfaction